French Tourism Imaginaries of Colombia - Sairi Piñeros (Via@)
Tourism imaginaries are very closely bound up with geographical imaginaries. They are constructed from the different information sources which we encounter in our everyday life. Various forms of media play an active role in disseminating information about locations. This article aims to unpack French tourism imaginaries of Colombia by analysing images of this country in media coverage. Analysis focuses on the image presented by television, the travel advice website of the French Ministry for Foreign Affairs, and comments shared by tourists on TripAdvisor.The article demonstrates the evolution of a tourism imaginary for a destination associated with negative images, the role played by media, and by tourists today, who can change these tourism imaginaries more rapidly by sharing their tourist experiences online and on social media.